Thermal diffusion and chemical reaction effects on unsteady flow past a vertical porous plate with heat source dependent in slip flow regime (Journal of Naval Architecture and Marine Engineering, 2016)
The present study investigates an analytical solution of free convective unsteady fluid flow in presence of thermal diffusion and chemical reaction effects past a vertical porous plate with heat source dependent in slip flow regime. The plate is assumed to move with a constant velocity in the direction of fluid flow, while free stream velocity is assumed to follow exponentially increasing small perturbation law. The velocity, temperature and concentration profiles are presented graphically for different values of the parameters entering into the problem. Finally the effects of pertinent parameters on the skin friction coefficient, Nusselt number and Sherwood numbers distributions are derived and have shown through graphs and tables by using perturbation technique.